The Relationship Between Principal Leadership and Work Motivation Teachers Based on Education and Da'wah - Syafaruddin, Baso; Mansur, Mansur; Yusuf, Yusuf (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study investigates the relationship between the principal's leadership and teacher motivation at public elementary school 1 Ranteanging. The research takes a qualitative approach, combining educational, psychological, and sociological aspects. Data were gathered through in-depth interviews, observations, and documentation and then analyzed using data reduction, presentation, and verification. The findings show that the principal uses successful leadership strategies, such as direct direction, motivation, and active participation in school activities. The principal is described as personable, disciplined, and adaptable, promoting good conduct and rewarding accomplishments. Teacher motivation has been highlighted as a key factor in increasing productivity and creating a positive work environment. Teachers that are highly motivated exhibit increased excitement and productivity, especially when backed by leadership that recognizes their achievements. The study suggests that the principal's leadership has a substantial impact on teacher work motivation, fostering a positive environment for professional development. We propose enhancing teacher performance management and classroom learning procedures to further develop this relationship. This study emphasizes the role of leadership in developing teacher motivation and the need for effective management techniques to maintain a productive educational environment.